2003
DOI: 10.1002/pbc.10410
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated thyroid carcinoma in childhood and adolescence—clinical course and role of radioiodine

Abstract: Prognosis of DTC in young patients was good. Patients with LR relapse and distant metastasis had a high rate of remission after treatment. RAI treatment can reduce the rate of LR relapse in patients with no distant metastasis and result in complete remission in half of those with distant metastasis. No patient experienced a second malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 50 publications
7
93
0
1
Order By: Relevance
“…As reported in our previous study, age O45 is an independent poor prognostic factor for LR FFS, DM FFS, and CSS (Chow et al 2002c). However, young patients of age !21 has higher rate of LR failures but better survival than age R21 (Chow et al 2004b). In this study, RAI improved LR control in patients with T1 or T2 disease with age %45, showing its efficiency in local control in low risk patients.…”
Section: Local Controlmentioning
confidence: 79%
“…As reported in our previous study, age O45 is an independent poor prognostic factor for LR FFS, DM FFS, and CSS (Chow et al 2002c). However, young patients of age !21 has higher rate of LR failures but better survival than age R21 (Chow et al 2004b). In this study, RAI improved LR control in patients with T1 or T2 disease with age %45, showing its efficiency in local control in low risk patients.…”
Section: Local Controlmentioning
confidence: 79%
“…Data available from the literature also demonstrate a higher frequency of lung metastases in children as compared with adult cases (32). In a recent series, Chow et al found pulmonary metastases in 15% of patients aged less than 21 years and 7.8% in the older individuals (33). In our experience, children with lung metastases usually have nodal disease with large thyroid nodules accessible by palpation without labored breathing in most instances.…”
Section: Clinical Course Of Childhood Patients With Thyroid Cancermentioning
confidence: 84%
“…Treatment with TTx, lymph node dissection, and RAI is considered appropriate for preventing recurrence (18,20,21,36). Chow et al (38) reported that RAI reduced the risk of both locoregional and distant recurrences. They did not detect secondary malignancy or impairment of fertility and pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%